2017
DOI: 10.1007/s10096-017-3001-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical condition and comorbidity as determinants for blood culture positivity in patients with skin and soft-tissue infections

Abstract: The utility of performing blood cultures in patients with a suspected skin infection is debated. We investigated the association between blood culture positivity rates and patients’ clinical condition, including acute disease severity and comorbidity. We performed a retrospective study, including patients with cellulitis and wound infection who had been enrolled in three Dutch multicenter studies between 2011 and 2015. Patients’ acute clinical condition was assessed using the Modified Early Warning Score (MEWS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 18 publications
3
20
1
2
Order By: Relevance
“…Just under half (47%) of the patients who died also received appropriate treatment after positive ESBL producing organisms, which underlines the fact that sensitivity and microbiology results cannot be interpreted without taking the patients' co-morbidity into consideration. This was also confirmed in a study done by Van Daalen et al 35 Overall, we believe our findings provide a stimulus to establish an antimicrobial stewardship team (ASTs) in this hospital, and likely in other hospitals in South Africa, to reduce inappropriate prescribing and dispensing and reduce AMR rates. 4 Coetzee and Brink underlined the importance of an antibiotic stewardship team and suggest that restrictive measures, even when perceived as punitive measures, may be required to influence future antibiotic prescriptions.…”
Section: Prescribing Practices After Positive Esbl Producing Results supporting
confidence: 87%
“…Just under half (47%) of the patients who died also received appropriate treatment after positive ESBL producing organisms, which underlines the fact that sensitivity and microbiology results cannot be interpreted without taking the patients' co-morbidity into consideration. This was also confirmed in a study done by Van Daalen et al 35 Overall, we believe our findings provide a stimulus to establish an antimicrobial stewardship team (ASTs) in this hospital, and likely in other hospitals in South Africa, to reduce inappropriate prescribing and dispensing and reduce AMR rates. 4 Coetzee and Brink underlined the importance of an antibiotic stewardship team and suggest that restrictive measures, even when perceived as punitive measures, may be required to influence future antibiotic prescriptions.…”
Section: Prescribing Practices After Positive Esbl Producing Results supporting
confidence: 87%
“…The use of blood or wound cultures in cellulitis management is debatable. Microbial outcomes are a poor indicator of treatment success as their yield is often low, even in the presence of infection, and they can be adversely affected if patients have been pretreated with antibiotics. Furthermore, microbial cultures do not correlate well with severity of signs and symptoms or patient experience .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, microbial cultures do not correlate well with severity of signs and symptoms or patient experience. 24 This outcome measure is also of limited relevance to patients. However, the increasing incidence of antimicrobial resistance means that other indicators of resistance, such as the incidence and severity of other bacterial infections, may be important to collect.…”
Section: Discussionmentioning
confidence: 99%
“…Cellulitis can lead to bacteremia and ultimately trigger sepsis development. The frequency of bacteremia in patients with cellulitis ranges from 2 to 21.3% among patients for whom blood cultures were available, depending on the study, setting and typology of the cases analyzed [4][5][6][7][8][9][10][11][12][13][14][15][16]. Taking into account that most cases of cellulitis are treated in the ambulatory setting and that blood cultures are not obtained in many hospitalized patients with less severe cellulitis, populations in which expectedly bacteremia occurs more infrequently, the overall prevalence of positive blood cultures considering the full spectrum of cellulitis would be even lower.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have shown that older age, male sex, diabetes, infected devices, alcohol abuse, cirrhosis, lymphedema and diverse other comorbidities increase the probability of bacteremia and, therefore, the performance of blood cultures in these patients would be advisable [9][10][11][12][13][14][15][16]18].…”
Section: Introductionmentioning
confidence: 99%